Recognition of Health Care Provider’s Patient Safety Culture in Kurdistan/Iraq - Ali, Ismail Ahmed; Hussein, Shewaz Abdalrahman; Ali, Shelan Omar; Muhamad, Fuaad Azad (Kurdistan Journal of Applied Research, 2022)
Globally, improving and promoting patient safety has been given a lot of attention in order to develop the standard of healthcare and conserve the clients from trauma. The study purposed to recognize the perception of the Health Care Provider (HCP) regarding patient safety culture. A quantitative design /descriptive method were carried out during the period from 12th to 24thJanuary 2019 at Rania teaching hospital. Data was collected through a hard copy self-managed survey form using the Hospital Survey of Patient Safety Culture (HSOPSC).Data was entered to SPSS and analyzed using descriptive and inferential statistics. The final study sample included 130 cases (74.5% response rate). The total mean positive answer rate for the hospital survey dimensions was (42.28%) with arrange of (79% - 4.6%). Approximately 60% of HCP was perceived patient safety culture practice negatively. However, only two dimensions from 11 had reached positive response rate by respondents which include teamwork within Units (76.2%) and organizational learning (79%) dimensions, while the lowest dimension’s positivity include the frequency of reporting errors (4.6%). Furthermore, more than half (64.6%) of the study sample estimated the grade of patient safety as agreeable level, also only two of the respondents (1.5%) rated excellent grades for patient safety in their hospitals. Almost, three fourths (75.8%) of study sample were reported that no events had reports in the previous year. Statistically, the results of the study showed a significant association among educational status (p=0.006), work areas (p=0.014), staff position (P=0.001), and mean score of HSOPSC. These findings demonstrated that attitudes and perception of HCP about patient safety culture is extremely low. Fundamentally, there is a necessity for systemic change at the level of health organization and continuous training course for HCP to improve patient safety culture are strongly recommended.